Effect of Different Row Spacing on Growth and Yield of Black Gram (Vigna mungo L. Hepper) under Khumaltar Condition - Neupane, Reshama; Timalsina, Himal Prasad; Bhattarai, Rajendra Kumar; Chaulagain, Bhimsen; Kaduwal, Sangita (Agronomy Journal of Nepal, 2025)
Blackgram (Vigna mungo L. Hepper) is an important summer grain legume in mid hills of Nepal. An experiment was conducted at National Agronomy Research Centre, NARC Khumaltar during 2022,2023 and 2024 to identify suitable row spacing for black gram. Five rows spacing (20 cm, 30 cm, 40 cm, 50 cm and 60 cm) and plant to plant spacing 10 cm were evaluated in randomized block design with four replications using variety Khajura Mash-1. Plot size of 12 m2 (4 m × 3 m) was maintained, and fertilizer dose applied was 20:40:20 N: P2O5:K2O kg ha-1. At physiological maturity, 10 plants per plot were sampled randomly for measurements of plant height, number of pods/plants, unfilled pods/plant and 100 seed weight. Data on days to 50% flowering, days to 90% maturity, plant height, number of pods per plant, biological yield and hundred seed weight were recorded. Combined analysis showed final stand/m2, number of branches per plant, harvest index and straw dry matter were found to be affected significantly by various row spacing. There was no any significant interaction effect between rows spacing × year. Year significantly influenced all the parameters except days to 50% flowering, days to 90% maturity and final stand/m2. The data of combined analysis of three years revealed that row spacing 20cm × 10 cm produced the highest grain yield (1746 kg ha-1) followed by 30cm × 10 cm (1725 kg ha-1). Similarly, the highest biological yield (10.5 t ha-1) was observed at 20 and 40 cm row spacing followed by 30cm (9.6 kg ha-1). Maximum harvest index (0.21) was provided by 60 cm row spacing followed by 30cm and 50cm (0.20). The finding concluded that maintaining 20 cm × 10 cm spacing was the better for higher grain yield and 30 cm × 10 cm was promising in better seed yield under Khumaltar, Lalitpur conditions.